Students’ Perceptions of the Educational Issue "Tertiary College Needs" and Efforts to Implement the Fifth Principle at the Higher Education Level - Muhammad, Iqbal; AnandaImam, Adli; AdeSiti, Aprila; AnnisaPutri, Apriliani; Asnita, Kartini; Dian, Algaven; Hermaulida, Lubis; JunikaHizkia, Adhycya; Miriam, Novika; Zaytuni, Nadya; Tamara, Angelsky; Ruth, Adeline; NabilaPutri, Adrian; Sabrina, Hidaiyah; Yesi, Rosalina; Yuli, Salwa (JUPE : Jurnal Pendidikan Mandala, 2024)
This study aims to explore students' perceptions of the issue of "tertiary education necessity" and the efforts to implement the Fifth Principle of Pancasila at the higher education level. Through a qualitative approach, in-depth interviews were conducted with students from various study programs at the State University of Medan. The results show that students' perceptions of tertiary education vary, with some agreeing, disagreeing, or strongly rejecting the statement. The research also reveals the importance of higher education in enhancing the quality of life and community welfare. Efforts to implement the Fifth Principle, such as scholarship programs and educational subsidies, are identified as crucial steps to ensure social justice and equitable access to higher education. This study is expected to contribute to the formulation of more inclusive and equitable educational policies.